(untitled) (Latakia University Journal -Biological Sciences Series, 2016)
نفذ هذا البحث لتحديد مدى أهمية استخدام مادة 1-MCP في إطالة العمر التخزيني لثمار الكاكي الياباني صنف "Hachiya" ، مع المحافظة على جودتها. تمت المعاملة بعد القطاف مباشرة بثلاثة تراكيز (0.5 ، 1 ، 1.5) ppm من مادة 1-MCP على درجة حرارة 20مْ لمدة 24 ساعة، ثم خزنت الثمار لمدة ستة أشهر ضن ظروف تخزينية ثابتة على درجة حرارة 2 مْ ورطوبة نسبية 85%. تم وبشكل دوري (كل شهر) أخذ عينات من ثمار كل معاملة لمعرفة التغيرات التي طرأت على مكوناتها خلال فترة التخزين. أظهرت النتائج أن الثمار المعاملة بمادة 1-MCP حافظت على قيم أعلى من الصلابة مقارنة مع ثمار الشاهد، كما قل الفقد بالوزن بشكل واضح بالنسبة لهذه الثمار خلال فترة التخزين. حدثت تغيرات في محتوى الثمار من فيتامن VC، الحموضة الكلية TA، لكن كل هذه التغيرات كانت منخفضة بشكل واضح في الثمار المعاملة بمادة 1-MCP , مقارنة مع ثمار الشاهد. تدل هذه النتائج على أن مادة 1-MCP مادة فعالة في إطالة العمر التخزيني (عمر الرف) لثمار الكاكي الياباني صنف "Hachiya". This research carried out to estimate the importance of use of 1-MCP in increasing shelf life of Japanese persimmon ,var (Hachiya) , and maintaining fruits quality. The fruits were treated with different concentrations of 1-MCP (0.5-1-1.5) ppm soonly after harvest at 20Cᵒ during 24 h, then stored for 6 months at controlled conditions (2Cᵒ and 85% of relative humidity). The samples were taken periodically (every month) to study the changes in fruits composition during storage period. The results showed that treatment with 1-MCP keeps fruits at higher degree of firmness compared to the control, and decreased the loss in weight at storage period.The treatment with 1-MCP decreased as well the changes in the fruits composition of Vitamine c, total acidity (TA) compared to the control. These results indicate that treatment with 1-MCP is effective in increasing shelf-life of Japanese persimmon fruits var (Hachiya).